Institui????es financeiras brasileiras e o esporte: o efeito do investimento em patroc??nio esportivo nos componentes do brand equity - Scombati, Daniel Pereira (2016)
Sport provides health, resilience, quality of life, team spirit, fairness, honesty and other qualities admired, and of course, tinkering directly with the passion enthusiast. Hereby, Brazilian financial institutions invest thousands of dollars in sponsoring sports activities to an improvement in their brand equity. Because of this, the present study aims at understanding through literature, document and quantitative research, the sports sponsorship can add value taken as positive the brand equity of financial institutions in Brazil. For this, we studied the five largest financial institutions in Brazil, as each of sponsoring the sport and what the effect of this sponsorship before consumers. For the achievement of the goal we used the sports sponsorship theories and brand equity, seeking to focus on the approach in the sports sector. descriptive quantitative methodology was used and achieved results confirmed the hypothesis of the work, that sports sponsorship has a positive influence on the brand equity components. This demonstrates the benefits for financial institutions, helping the market gain competitive advantage and have a valued image of heritage and always present on the consumer.